Obshcheprofessional'naya distsiplina "Menedzhment v fizicheskoi kul'ture i sporte": Problemy, puti ikh resheniya, perspektivy (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The aim of this paper was to discuss the problems of development in the general professional discipline «Management in Physical Culture and Sport» at the higher physical culture educational institutions of Russia. The authors offer two main approaches to improve the quality of education in that course of management, the extensive and the intensive ones and offer the classification of its conditions and subprogrammes.